Pentingnya Peranan Guru Pendidikan Agama Kristen Meningkatkan Minat Membaca Alkitab Bagi Peserta Didik Kelas VII Di SMP Negeri 1 Teriak Kabupaten Bengkayang - Viter Viter; Daniel Marciano Kapoh; Lukas Budi; Marthen Mau (Jurnal DIKMAS, 2025)
Christian religious education at SMP Negeri 1 Teriak is an effort made to increase interest in reading the Bible for students in class VII, which is very important by increasing their reading of the Bible so that they can understand the meaning of the Bible. This type of research is qualitative research with an approach through observation, interviews, documentation, library research. The results of the research show that the efforts of Christian religious education teachers to increase interest in reading the Bible for class VII students at SMP Negeri 1 Teriak, Bengkayang Regency are: 1) implementing literacy before starting lessons; 2) provide questionnaires for weekly reports at church; 3) give memory verses for each homework assignment; 4) create stories using Bible sources and are required to read the Bible every day to make reports. So, PAK teachers play an increasingly important role in encouraging Class VII students to read the Bible, so students will increasingly increase their interest in reading the Bible.